“Cuanticación de biomasa y carbono secuestrado en un sistema agroforestal de cacao (theobroma cacao L.) en tarapoto-San Martín” - Vilchez Novoa, Edin (2014)
To global scale the change of use of the land and the forest activities have been, and are nowadays clear sources of emission of carbon dioxide in the atmosphere. Nevertheless with a suitable managing, the human beings we have the potential to change the direction of the flows of carbon between the soil and the atmosphere; and parallel there would be provided multiple environmental and socioeconomic benefits by means of the payment by environmental services, achieving this way the goals of the sustainable development as well as the mitigation of the global effects of the climate change. The present thesis had as principal aim generate technical scientific information base far the project formulation of credit commercialization of carbon, in the frame of the Protocol of Kyoto, by means of the system utilization agroforestales of cocoa in the Peruvian Amazonia. In addition the present test seeks to contribute with the generation of technical information of database to the project formulation of credit commercialization of carbon, by means of the system utilization agroforestales of cocoa in the Peruvian Amazonia, as sinks of greenhouse gases and as possible engine of development to the producers cacaoteros. There was in use a descriptiva and comparativa statistics, which has as intention quantify the reservation of carbon in a system agroforestal with cocoa (Theobroma cocoa L.) Tarapoto San Martín. This study was realizad in the demonstrative plots of the lnstitute of Tropical Cultures (E.E Juan Bernito), located to 2.5 km from Tarapoto, in the District of the Band of Shilcayo, Sector Lagoon Venice (transectos 1, 2, 3, 4). The results show the reservations of carbon for every type of air biomass and of the soil in the evaluated plot, it is so the major content of biomass met in the verbiage 38.71 tn.ha-1, followed by the arboreal alive species 10.34 t.ha-1, the fallen dead trees 7.34 tn.ha-1 and arbustivas/herbáceas 1.95 tn.ha-1. With regard to the total average content of air biomass (58.54 tn.ha-1) found in the system agroforestal with cocoa, 66.12 % was in the verbiage for effect of abscission of the leaves of the cocoa, 17.66 % the arboreal alive species, 12.54 % in fallen dead trees and 3,33 % in the species arbustivas and herbaceous found in the system. The major content of carbon met in the verbiage 17.42 tn.ha-1, followed by the arboreal alive species 4.65 tn.ha-1, the fallen dead trees with 3.30 tn.ha-1 and arbustivas/herbáceas with 0.88 t.ha-1 and with a percentage relation it is 66.36 % for the verbiage, 17.74 % for the arboreal alive biomass, 12.57 % for the fallen dead trees and 3.35 % for the biomass arbustiva/herbácea considering the average of 100 % of the content of carbon that was of 26.25 tn.ha-1. The average contents obtained in organic matter (MO) and organic carbon (CO) it was a function of the depth of the soil, which 1 involve values of regression of-0.401 and-0.247 4 for him % of organic matter (MO) and the % of organic carbon (CO) in the soil respectively. lt does not exist a logical sequence of the content of carbon for horizon in relation to the % of CO and % of M.O. did not involve a logical relation depending on the depth of the soil but of the volume of the horizon and his apparent density, deciding so the treatment (horizon) between 40 and 100 cm with a volume of 28, 129. 48 m3 threw a content of 23.88 tn.ha-1 of C, followed by the horizon between O and 1 O cm with a volume of 4,244.27 m3 with 14.098 tn.ha-1 of C, the horizon between 20 and 40 cm with a volume of 9,038.83 m3 with 12.035 tn.ha-1 of C and the horizon between 10 and 20 cm with a volume of 4,633.90 m3 with an average of 8.383 tn.ha-1 of C total in the soil respectively. Words claves: Transecto, biomass, greenhouse effect.